Lipid profile of in vitro embryos produced from Bos indicus cows with low and high antral follicle counts - Rosa, Camila Oliveira; Costa, Camila Bortoliero [UNESP]; de Lima, Camila Bruna; da Silva, Camila Bizarro; Zangirolamo, Amanda Fonseca; Ferreira, Christina Ramires; Seneda, Marcelo Marcondes (Elsevier, 2021)
The quantity of lipids available for the initial development processes of in vitro-produced (IVP) embryos can reflect directly on embryonic quality and pregnancy rates. Therefore, the objective of this study was to investigate the lipid profile of IVP embryos from Bos indicus females with different antral follicle counts (AFCs). For this purpose, ovaries from 149 Nelore females were collected at a local slaughterhouse and transported to the laboratory. AFC was determined by visual follicle counting on the surface of both ovaries of each animal. The animals were classified as low AFC (≤ 31 follicles; mean less SD) and high AFC (≥ 92 follicles; mean plus SD). Oocytes were matured, fertilized and cultured in vitro. Cleavage and blastocyst rates were evaluated on days 3 and 7, respectively. Blastocysts collected on day 7 (D7; n = 18 per group) were subjected to lipid profile analysis by desorption electrospray ionization-mass spectrometry (DESI-MS). In vitro production rates were evaluated by logistic regression using the Car R statistical package (R Development Core Team – 2008), and the differences were considered significant at P < 0.05. For lipid profiling, principal component analysis (PCA) followed by Fisher's test was used. There were no differences between groups regarding the cleavage (78.9% in high AFC vs. 79.5% in low AFC) or blastocyst rates (41.7% in high vs. 40.3% in low AFC). The embryos derived from high-AFC cows presented a higher concentration of lipids in the category of TAG than the embryos from low-AFC females. In contrast, embryos from low-AFC donors had the highest concentrations of cholesterol and its derivatives and DAG. In conclusion, the lipid profile of embryos generated from ovaries with a low AFC is different from that of embryos generated from ovaries with a high AFC despite similar IVP rates. Our results may support studies related to the influence of lipid content on embryonic development and viability.
Keywords: Antral follicle count; Bos indicus; DESI-MS; Embryos; In vitro